PERLINDUNGAN HUKUM TERHADAP HAK PENGELOLAAN DAN PEMANFAATAN ATAS TANAH OLEH MASYARAKAT HUKUM ADAT YANG BERADA DALAM KAWASAN TAMAN NASIONAL KELIMUTU - Christiana Sri Murni; Yohanes Pande; Bernadus B. Kelen (Trunojoyo Madura University, 2023)
The establishment of the zoning of the Kelimutu National Park by the relevant agencies resulted in the management of the forest area being closed to the access of the Customary Law community as the owner of agricultural/plantation land in Niowula Village, Detusoko District, Ende Regency and this is detrimental to the community. In this regard, this study aims to examine how customary forests are regulated in the versions of regulations before and after the Constitutional Court Decision No. 35/PUU-X/2012. This research is a normative research using a statutory approach. The existing primary and secondary legal materials were then subjected to a qualitative juridical analysis. The results of the study show that the constitution requires conflict resolution to be carried out using a functional approach and a human rights approach, but in fact the use of a human rights approach creates a conflict between the rules under the constitution and the constitution. This requires the government to harmonize regulations because there are still many regulations which are very dominant with a functional approach, and very little use of a human rights approach.